Inovasi Pengelolaan Sampah Menggunakan “Rocket Stove” Sebagai Solusi Sampah Non Organik - Aldy Reynaldy Leuwyh; Muhammad Ridho Fudoil; Putri Cahyani; Dedy Khaerudin; Budiharjo Budiharjo; Ganjar Sidik Ganjara (BADAN PENERBIT STIEPARI PRESS, 2025)
The problem of non-organic waste that is difficult to decompose has become a significant environmental issue in various regions, both urban and rural. To answer this challenge, the student team of the Student Work Lecture (KKM) 41 Year 2025 together with lecturers from the Industrial Engineering Study Program carried out community service activities in Mekarsari Village by designing and building waste incinerators based on appropriate technology, namely environmentally friendly and low-smoke rocket stoves. This activity was carried out through several stages, including initial surveys, location mapping, tool development, and evaluation of effectiveness by the local community. The rocket stove developed is designed to withstand combustion temperatures of up to 4000°C, with chimney temperatures ranging from 2000°C to 2500°C, and a maximum burning time of only 20 minutes. This efficiency shows that the combustion process takes place optimally. The sealed design with tight insulation using cement and hebel materials makes this tool safe, efficient, and environmentally friendly. This technology not only significantly reduces the volume of non-organic waste, but also reduces the impact of air pollution due to combustion fumes. Through a participatory and educational approach, the people of Mekarsari Village are actively involved in the process of building and utilizing tools, so that collective understanding and awareness of the importance of sustainable waste management is created. The results of this activity are expected to be an applicative solution in non-organic waste control at the local level, and can be replicated in other regions with similar characteristics. Thus, this service activity contributes to environmental preservation and improving the quality of life of the community through appropriate technological innovations.